Three Essays on Foreign Trade, Offshoring and International Rivalry - Lei, Weng Chi (University of Washington, 2018)
This dissertation consists of three essays, covering the topics of foreign trade, offshoring and international rivalry. In particular, Chapter 1 analyzes the strategic capacity allocation of an international oligopoly. Because a line of products shares specific inputs that are fixed in the short run, a multiproduct oligopolist faces a capacity constraint in the production. Not being able to produce the desirable quantities to meet demand, an oligopolist strategically allocates its capacity among different products against its rival. If the market were monopolistic, a firm would mainly concern the effective profitability of a product when allocating its capacity and when responding to a capacity expansion. Identical duopolists that compete in a Cournot fashion should have identical capacity allocation. However, in a sequential game, while the Stackelberg leader allocates all its scarce capacity towards the more profitable product, the follower should still allocate some capacity towards the unprofitable product. This matches the observation that Boeing, the incumbent in the large commercial aircrafts (LCA) industry, specializes in smaller planes, while Airbus allocates resources more evenly towards both superjumbo planes and smaller planes. Chapter 2 provides an explanation to the observation that international oligopolists, which are similar in many ways (subject to the same state of technology, have equal market shares, etc.), may engage in significantly different degrees of offshoring. Different from previous studies, which considered fragmentation to be affected by global exogenous factors only, this essay sees fragmentation as an endogenous variable. A firm can invest on R&D of its own fragmentation technology to enable certain degrees of fragmentation, so that offshoring of those fragmented subparts can be achieved. An important implication of endogenous fragmentation is that the government now has a policy alternative to export subsidy. Very often, when export subsidy is prohibited under an FTA, a government has incentive to subsidize fragmentation of a firm, which can stimulate both export and offshoring. Chapter 3 investigates Macao's and Singapore's questionable goal to diversify among two tourism services—gambling and convention. Macao has a cost advantage in gambling while Singapore has a cost advantage in convention. When a city operates as a regional monopoly, the simple multiproduct model shows that it is optimal for a city to diversify in response to an expansion in the markets of the tourism services. If the two cities operate as a Cournot duopoly instead, there will be a higher degree of product differentiation between the cities. Yet, both cities diversify more when there is a market expansion. On the other hand, Osaka is a potential entrant. The three-city model shows that if Osaka's relative cost of producing convention is even lower than Singapore’s, both Macao and Singapore will produce greater proportions of gambling compared to the two-city case. In general, Macao and Singapore respond to Osaka’s rivalry by strategizing their product mixes to avoid head-on competition with Osaka.
Keywords: 0501:Economics; Economics; Foreign trade; International rivalry; Offshoring; Social sciences; Strategic capacity allocation

Oligopolistic Strategies in the Gaming and Hospitality Industries of Macau - Leong, Chi Leng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Mandatory Provident Fund Scheme: Prespectives of Macau Employees - Cheong, Kit I. (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

IMPACTS OF CHINA’S ENTRY ON THE PRODUCT LINE RIVALRY IN THE GLOBAL CIVIL AIRCRAFT INDUSTRY - Chen, Yawen (University of Saint Joseph, 2024)
As international tourism continues to flourish and airlines are eager to expand their fleets, the demand for civil aircraft has continues to grow in the global market. The market has been a duopolistic one, shared by Boeing and Airbus. However, the recent entry of the Chinese company, Comac, had the potential to turn it into a triopoly within certain segment of the product line. This observation motivates the research objective to analyze the impact of Comac's entry on the production strategies of the incumbents. Specifically, this dissertation studies the impact on each firm’s allocation of production capacity toward different civil aircraft in the product line in response to how Comac’s entry, which can also impact the effects of capacity increase and market expansion on the product line rivalry. This dissertation is based on a multi-product, oligopolistic model of Boeing and Airbus. To provide insights on the strategy and behavior of each firm in the evolving competitive environment, this dissertation solves and extends the mathematical model to incorporate Comac as the entrant and compares model results with data of orders and deliveries of the three companies in the past 15 years. This model finds that when Comac's C919, a relatively small plane, enters the global civil aircraft market, Boeing and Airbus will increase the production of their small planes and decrease the production of the relatively large planes under the production capacity constraints. If the production capacity increases, both Boeing and Airbus will produce more planes, but will allocate more additional capacity to large planes than to small planes compared to the duopolistic competitive environment. When the market demand increases, despite the entry of the C919, Boeing and Airbus iv will continue to increase the production of both large and small planes, but the response is greater to an increase of demand for large planes than that for small planes. The orders and deliveries data provide some but insufficient support for the model predictions. As the market participation of Comac continues to grow, future researchers can re-assess the models’ propositions with more available data
Keywords: Capacity allocation; Civil aircraft; Comac; Duopoly; Oligopoly; Product line rivalry; Thesis and Dissertations Master of Business Administration (MBA); Triopoly; University of Saint Joseph

IMPACTS OF CARBON TRADING SYSTEM ON GREEN FINANCE: Ziyan Yin - Yin, Ziyan (University of Saint Joseph, 2024)
Against the backdrop of escalating global climate change and China being the world’s largest carbon emitter, this study explores the impact of the carbon trading system on green finance in Chinese power sector. This study uses a quantitative research method, namely a difference-in-differences (DID) model, to investigate power companies that participated or had the potential to participate in carbon trading in 2019 and 2022. The key finding is that companies that participated in carbon trading had significantly higher green finance than those that did not participate, indicating that the carbon trading system has a positive impact on promoting green finance. However, the impact does not significantly intensify after the national carbon trading scheme was implemented in mid-2021. The green finance of listed companies and state-owned enterprises were less affected by carbon trading, possibly because these companies rely on alternative financing options and government financial support. Due to the findings, this study recommends that policy makers should strengthen the promotion of the carbon trading scheme and provide more support for non-listed companies and non-state-owned enterprises. At the same time, the companies should actively participate in the carbon market to take advantage of the industrial policies to enhance green finance, and ultimately promote environmental protection and their own sustainable development
Keywords: Carbon trading scheme; Carbon trading system; China; DiD; Difference-in-difference; Green finance; Power companies; Power plants; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

Fintech Services in Guangdong-Macao in Depth Cooperation Zone in Hengqin: An investigation of Macao Users' Adoption - Kuan, Chi Hou (University of Saint Joseph, 2022)
Keywords: Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph

EVALUATING SATISFACTION OF LOCAL ROAD USERS OF MACAU - Fong, Chi Cheng; Pinheiro, Francisco Vizeu; Lei, Weng Chi (University of Saint Joseph, 2023)
"Macau's rapid economic development in recent decades and relatively low usage of public transportation have put considerable pressure on the city's carrying capacity. Improving the transportation system has been a major policy goal of Macau's urban planners. To deepen the understanding of the perspectives of local road users, this dissertation's main research question is: what factors determine the satisfaction of local road users of Macau? After collecting responses using an online questionnaire, quantitative research methods were adopted to analyze travel patterns, satisfaction toward different road usage dimensions, and sociodemographic characteristics of local residents. 145 responses were collected and quota samples were generated to match the distribution of each sociodemographic feature of the population. Most respondents used private vehicles to travel during peak hours on weekdays for work or for school and to travel during the entire afternoon and evening on weekends for shopping necessities and for leisure. The most traveled districts were Baixa de Taipa, Costa & Ouvidor Arriaga, and Baixa de Macau. It was found that the mean overall satisfaction score inclined to the dissatisfaction side (below 3). Only clarity of traffic lights and number of road signs (measuring infrastructure) and temperature and price of fares (measuring public transportation) had mean satisfaction scores that were significantly higher than 3, indicating higher satisfactions. Meaningful hypotheses regarding the differences of different road user groups were set out, then Kruskal-Wallis ANOVA tests and Mann-Whitney U tests were run. The significant findings were such that the elderly aged 65 or above were less satisfied and the unemployed were more satisfied with road usage. The better educated were more satisfied with the environment, and the unemployed were more satisfied with the public transportation. Drivers were less satisfied with transportation costs, and peakhour road users were less satisfied with the infrastructure. The Spearman correlation analyses found that infrastructure had moderately positive correlation with facilities and with travel safety. Based on the findings and their policy implications, policy suggestions could be made. The policies suggested in this study should have favorable short-term and long-term effects on more than one road usage aspects."
Keywords: Public transport; Survey questionnaire; Thesis and Dissertations Master of Government Studies (MGS); Traffic congestion; Transportation; Transportation services; University of Saint Joseph

Attitudes, Acceptance, and Registration toward Organ Donation in Macao - Lou, Kin Heng (University of Saint Joseph, 2021)
Keywords: Thesis and Dissertations Master of Government Studies (MGS); University of Saint Joseph

Anti-money laundering in the Greater Bay Area: effectiveness, strategies and compliance - Hoi, Kuan Io (University of Saint Joseph, 2019)
Keywords: Theses and Dissertations Master of Business Administration (MBA); University of Saint Joseph

A STUDY OF GREEN FINANCIAL TECHNOLOGY ACCEPTANCE IN TONGZHOU DISTRICT OF BEIJING - An, Bo Yang (University of Saint Joseph, 2023)
China’s economy has entered a critical period of structural adjustment. The developing green industries and the transforming traditional industries have increasing demand for finance, making ""green finance"" increasingly essential. While China's green finance is in the development stage, some newly developed zones serve as pilots for the launch of green financial products. An example is Tongzhou District of Beijing, which aims to expand Beijing’s space, promote the coordinated development of Beijing-Tianjin-Hebei, and explore the optimal development mode of the densely populated economic areas. This thesis aims to study consumer acceptance of green financial technology (fintech) in the case of Tongzhou District. This thesis extended the commonly applied theoretical model for the problem of study, the Energy Augmented Technology Acceptance Model (EA-TAM), to analyze the impacts of perceived usefulness, perceived ease of use, attitude toward use, intention, usage intention, environmental awareness, and green knowledge on the acceptance of green fintech in Tongzhou District. The survey collected 403 valid responses from people that had been active in Tongzhou District. The quantitative analysis is based on structural equation modeling techniques, including reliability analysis, validity analysis, standard method deviation test, and hypothesis testing. The analytical results show that all the hypothesized factors are significant. In addition, the sample is divided into different gender groups and education groups, so that the impacts of the socio-demographic characteristics can be explored. Males’ environmental awareness and green knowledge are insignificant in determining their acceptance of green fintech. The low-educated group’s acceptance of green fintech does not significantly depend on environmental awareness and perceived usefulness
Keywords: Fintech; Green Gintech; Thesis and Dissertations Master of Business Administration (MBA); University of Saint Joseph